The history of Aristotelian society of the early period: the genesis and preconditions for development - R. A. Yuriev (Омский научный вестник: Серия "Общество. История. Современность")
The study presents the early period of the history of the Aristotelian society on the basis of the theoretical principles of network analysis by Randall Collins. The theoretical basis of network analysis has significant heuristic capabilities and help to understand the process of development of the Aristotelian Society, which has turned from a group of philosophy enthusiasts into a professional philosophical association. It is emphasized that quantitative criteria of periodization are problematic because they do not take into account the complex intellectual atmosphere in British philosophy of the late XIX–early XX century. The article discusses popular historical and philosophical cliches that simplify the reflection of this period only as an arena of rivalry between British idealists and analytical philosophers. The important role of Shadworth Hodgson as the first president of the Aristotelian Society is also considered.